Comparative evaluation of stress levels before, during, and after periodontal surgical procedures with and without nitrous oxide-oxygen inhalation sedation - Gurkirat Sandhu; Paramjit Kaur Khinda; Amarjit Singh Gill; Vineet Inder Singh Khinda; Kamal Baghi; Gurparkash Singh Chahal (Wolters Kluwer Medknow Publications, 2017)
Context: Periodontal surgical procedures produce varying degree of stress in all patients. Nitrous oxide-oxygen inhalation sedation is very effective for adult patients with mild-to-moderate anxiety due to dental procedures and needle phobia. Aim: The present study was designed to perform periodontal surgical procedures under nitrous oxide-oxygen inhalation sedation and assess whether this technique actually reduces stress physiologically, in comparison to local anesthesia alone (LA) during lengthy periodontal surgical procedures. Settings and Design: This was a randomized, split-mouth, cross-over study. Materials and Methods: A total of 16 patients were selected for this randomized, split-mouth, cross-over study. One surgical session (SS) was performed under local anesthesia aided by nitrous oxide-oxygen inhalation sedation, and the other SS was performed on the contralateral quadrant under LA. For each session, blood samples to measure and evaluate serum cortisol levels were obtained, and vital parameters including blood pressure, heart rate, respiratory rate, and arterial blood oxygen saturation were monitored before, during, and after periodontal surgical procedures. Statistical Analysis Used: Paired t-test and repeated measure ANOVA. Results: The findings of the present study revealed a statistically significant decrease in serum cortisol levels, blood pressure and pulse rate and a statistically significant increase in respiratory rate and arterial blood oxygen saturation during periodontal surgical procedures under nitrous oxide inhalation sedation. Conclusion: Nitrous oxide-oxygen inhalation sedation for periodontal surgical procedures is capable of reducing stress physiologically, in comparison to LA during lengthy periodontal surgical procedures.